Developing Teaching Competences With Service-Learning Projects - Sartor-Harada, Andresa; Azevedo-Gomes, Juliana; Torres-Simón, Ester (Journal of Higher Education Outreach and Engagement, 2023)
Service-learning (SL) is an active methodology built onto reciprocal learning that combines social responsibility and academic learning. Changes in students’ profiles and the evolving interaction between educational institutions and society have encouraged the use of similar participative methodologies in diverse contexts, including higher education. Although the focus of these projects usually centers on student learning, SL experiences enable a holistic construction of knowledge that also affects instructors. This study analyzes instructors’ perceptions on developing teaching competences in SL projects and overcoming difficulties. The current research, based on a mixed paradigm, collected answers to a semistructured questionnaire from university instructors (n = 34) in 12 Ibero-American countries with experience in SL. The results show how instructors rate positively their acquisition of teaching competences (socioemotional, organizational, and technical competences) when organizing SL projects; however, they experience a lack of training in this specific methodology.
Keywords: higher education; service-learning; teaching competences; Scopus